Building Cisco remote access networks (Rockland, MA : Syngress Media, 2000)
An increasing number of companies are designing and implementing Remote Access Networks, which allow users who are not physically connected to a Wide Area Network (WAN) or Local Area Network (LAN) to access the network's servers, applications and databases or to participate in video conferencing and conference calls. The ability for a remote user to function as if they were in the next office dramatically improves overall efficiency while reducing total cost of ownership. Cisco Systems, the world's largest internetworking vendor, is the pioneer of the enabling technologies for Remote Access Networks. This book will identify and explain all of the Cisco products necessary for designing and building a remote access network and integrating it with legacy systems. This book is a professional reference detailing all of the strategies, tactics and methods for designing, configuring and maintaining Cisco Remote Access Networks. It will include thorough discussions of all Cisco Access Servers and routers. * Demand for information on remote access networks is growing quickly at corporate and administrator level * Cisco remote access networks appeal to businesses as they provide efficient and secure connectivity at reduced cost * Book includes thorough discussions of all Cisco Access Servers and routers.
Includes index.
Keywords: Computer terminals -- Remote terminals; Computer network; Cisco Systems, Inc. (Firm); Electronic books